Learn PowerShell in a month of lunches ; covers Windows, Linux, and macOS - Petty, James; Plunk, Travis; Leonhardt, Tyler; Jones, Don 1971-; Hicks, Jeffery (Manning Publications, 2022)
Learn PowerShell in a Month of Lunches, Fourth Edition is a new edition of the bestseller that introduced PowerShell to over 100,000 readers. With bite-sized lessons and hands-on exercises, this amazing book guides you from your first command to writing and debugging reusable scripts for Windows, Linux, and macOS. Set aside just an hour a day and you'll soon be tackling increasingly complex automation tasks with PowerShell.
Online resource; title from title details screen (O'Reilly, viewed July 23, 2024)
Keywords: Windows PowerShell (Computer program language); Computer programming; Windows PowerShell (Langage de programmation); Programmation (Informatique); computer programming; Audiobooks; Livres audio